2017
DOI: 10.3892/ol.2017.6432
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and invasion of ovarian cancer cells are suppressed by knockdown of TRIM11

Abstract: Tripartite motif-containing (TRIM)11, an E3 ubiquitin ligase, is involved in the development of the nervous system. As an oncogene, it has also been identified in glioma, lung and colon cancer. However, few studies have been conducted on TRIM11 expression and functions in ovarian cancer. In the present study, we found that TRIM11 expression was obviously elevated in ovarian cancer tissues compared to adjacent non-cancerous tissues. Depletion of TRIM11 in A2780 and SK-OV-3 ovarian cancer cells by transfection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…It has been demonstrated that TRIM11 upregulation contributes to the growth and metastasis of hepatocellular cancer cells as well as ovarian cancer cells [21,22]. In the present analysis, TRIM11 silencing deeply suppressed the proliferation and improved the apoptosis of OS cells.…”
Section: Discussionsupporting
confidence: 49%
“…It has been demonstrated that TRIM11 upregulation contributes to the growth and metastasis of hepatocellular cancer cells as well as ovarian cancer cells [21,22]. In the present analysis, TRIM11 silencing deeply suppressed the proliferation and improved the apoptosis of OS cells.…”
Section: Discussionsupporting
confidence: 49%
“…Tripartite motif-containing protein 11 (TRIM11), encoded by the TRIM11 gene, is an E3 ubiquitin ligase. Recent studies have demonstrated that the expression levels of TRIM11 are increased in gliomas [13], ovarian cancer [14], and lung cancers [8]. These studies have shown that TRIM11 has a role in regulating the development of human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TRIM11 expression was reported to be increased in high-grade gliomas and to have an oncogenic role and to be associated with the progression of glioma [13]. Chen et al showed that TRIM11 was upregulated in ovarian cancer tissue, and that knockdown of the TRIM11 gene suppressed proliferation and induced apoptosis of cancer cells [14]. Also, the overexpression of TRIM11 has been shown to promote cell proliferation, migration, and invasion of lung cancer cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other TRIMs, although do not exert a specific role in the regulation of cell cycle phase transitions, are yet involved in controlling carcinogenesis and cancer progression (Table 1). Most of these TRIMs, like TRIM11 [70,71,72,73,74], TRIM23 [75], TRIM24 [76], TRIM25 [77,78,79], TRIM31 [80], TRIM37 [81], TRIM47 [82,83], TRIM65 [84], and TRIM71 [85] are up-regulated in cancer cells and tissues, playing an oncogenic role in different types of cancer. These TRIMs are often associated with unfavorable prognosis and promote cancer cells proliferation and migration, being often associated with proteins of central signaling pathways.…”
Section: Trims and Cell Cycle Progressionmentioning
confidence: 99%